Bioinformatics Analysis of Rho GTP-ase Activating Protein 35 (ARHGAP35) in Breast Cancer Migration - Febrian, Dicky Rizky; Setyono, Joko; Fareza, Muhamad Salman; Choironi, Nur Amalia; Fadlan, Arif; Sarmoko, Sarmoko (Indonesian Society for Cancer Chemoprevention, 2021)
Breast cancer is a second deadly cancer after lung cancer worldwide. Progression of cancer is driven by mutated cancer drive gene such as ARHGAP35. This study aims to analyze the role of ARHGAP35 in the growth and development of breast cancer cells. ARHGAP35 expression level was analyzed using Oncomine (p-value<1E-4; gene rank top 10%). Overall survival (OS) and disease-free survival (DFS) were evaluated by using GEPIA (median cutoff; HR displayed with 95% CI). STRING was used for analyzing the protein-protein interaction network, while WEBGESTALT for KEGG pathway and gene ontology (GO) of ARHGAP35 and associated proteins and cBioPortal for gene mutation. ARHGAP35 was overexpressed in several types of breast cancer, namely invasive ductal breast carcinoma (IDC), invasive ductal and lobular breast carcinoma (IDLC), invasive lobular breast carcinoma (ILC), male breast carcinoma, and mixed ductal and lobular carcinoma (MDLC). High expression of ARHGAP35 had significantly lower OS (p=0.045) compared to low expression of ARHGAP35 and the difference in DFS was not significant (p=0.98). ARHGAP35 interacted with RHOA, RHOB, RHOC, RHOD, RASA1, RND1, RAC1, CDC42, FYN and SRC. KEGG pathway and GO analysis showed that these proteins are highly involved in actin-based processes through adherent junction, axon guidance, focal adhesion, regulation of actin cytoskeleton, and tight junction. Mutation rate analysis showed 34 missense, 29 truncating, 3 fusion, and 1 in frame on ARHGAP35. Taken together, ARHGAP35 may involve in the growth and development of breast cancer through regulation of actin cytoskeleton pathway.Keywords: ARHGAP35, breast cancer, KEGG pathway, mutation rate, actin cytoskeleton.